Study and development of mobile application and communication system for natural disaster - Fazira, Nan (Universiti Malaysia Sarawak (UNIMAS), 2017)
Natural disasters have caused negative impacts to human lives, national economy and structure. An efficient and practical management of early warning system plays a vital role in reducing the impacts of natural disasters to human population.. Some developing countries like Malaysia is facing a difficulty in implementing an expensive and complicated early warning system which had already implemented in other developed countries. Thus, the proposed project of Natural Disaster Alert System is a low-cost early warning system that consists of a cheap microcontroller to process the sensor data, Wi-Fi shield to transmit sensor data from microcontroller to online database, GSM shield to send alert in the form of SMS and a free android application. The communication system which is applied in this proposed project allows the sensor data to be stored in an online database rather than in the microcontroller's memory. Users will receive the alert notification via mobile phone application and SMS whenever a natural disaster event occurs near them.